2019
DOI: 10.1097/ccm.0000000000003829
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Critical Care Admissions and Cognitive Trajectories in Older Adults*

Abstract: Objectives: Patients requiring admission to an ICU may subsequently experience cognitive decline. Our objective was to investigate longitudinal cognitive trajectories in older adults hospitalized in ICUs. We hypothesized that individuals hospitalized for critical illness develop greater cognitive decline compared with those who do not require ICU admission. Design: A retrospective cohort study using prospectively collected cognitive scores of participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…In addition, it is consistent with previous studies that reported that cognitive impairment experienced by critical care survivors had a higher incidence and longer duration than other areas of PICS [27][28][29]. The major risk factor for cognitive impairment is known as delirium [30], so ICU medical staff apply various interventions to prevent delirium. Recently, the use of ABCDEF Bundle has been recommended [31].…”
Section: Discussionsupporting
confidence: 89%
“…In addition, it is consistent with previous studies that reported that cognitive impairment experienced by critical care survivors had a higher incidence and longer duration than other areas of PICS [27][28][29]. The major risk factor for cognitive impairment is known as delirium [30], so ICU medical staff apply various interventions to prevent delirium. Recently, the use of ABCDEF Bundle has been recommended [31].…”
Section: Discussionsupporting
confidence: 89%
“…11 Health Services Research Network in Chronic Diseases (REDISSEC), Barcelona, Spain. 12 Mental Health Department, Parc Taulí Hospital Universitari, I3PT, UAB, Sabadel, Spain. 13 Department of Psychiatry and Forensic Medicine, Universitat Autònoma de Barcelona, Bellaterra, Barcelona, Spain.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Cognitive impairment in critically ill survivors who have undergone invasive mechanical ventilation (MV) during the Intensive Care Unit (ICU) stay is a well-established health problem [1][2][3][4][5][6][7][8][9][10][11]. ICU admission is associated with a greater cognitive decline than general ward hospitalization [12], and the rate of dementia diagnosis after 3 years of follow-up has been reported to be higher in elderly ICU survivors than in the general population [13]. This cognitive decline affects the functional and socioeconomic status of ICU survivors and their families, and reduces their quality of life after ICU discharge [5,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospitalizations for both critical and noncritical illness are associated with long‐term cognitive decline in older adults 1‐8 . The public health implications of cognitive impairment in older adults after hospitalization are considerable.…”
Section: Introductionmentioning
confidence: 99%